IMPLEMENTATION OF DIFFERENTIATED LEARNING MODELS IN THE INDEPENDENT CURRICULUM IN INDONESIAN LANGUAGE LEARNING IN PRIMARY SCHOOLS - Elma - Yuniarti (Jurnal Ilmiah Madrasah, 2025)
Merdeka Belajar places a high value on a curriculum that may develop students' creativity by using strategies and techniques that develop critical thinking skills. A diversified learning approach is included in the Merdeka curriculum as an attempt to modify the classroom learning process to fit the needs of the pupils. Differentiated learning is an approach to education that considers the learning profiles, interests, talents, and readiness of each student. This study aims to investigate the use of differentiated learning in the Merdeka curriculum, specifically in the context of Indonesian language instruction in elementary schools, as well as the effects of such an implementation on primary school pupils. In order to provide a literature evaluation about the implementation of differentiated learning in elementary schools and its applicability to the implementation of the Independent Curriculum, a descriptive qualitative research approach that combines many literature studies was employed. The study's findings indicate that, in implementing differentiated learning, MI Tarbiyatussibyan Banyuwangi's students' needs were determined by means of assessments. This allowed for a more student-centered learning process, which improved students' ability to participate more actively in class. and for teachers to apply personalized learning with greater creativity and innovation. Personalized education Where pupils may assess themselves because diverse learning requires teachers to be able to comprehend the unique qualities of every student; they cannot equalize because every student is unique and has unique talents. Students at MI Tarbiyatussibyan Banyuwangi have benefited from the implementation of differentiated learning in Indonesian language courses. Students respond positively to the lessons they have learned, feeling that the material is easy to understand and that there has been a beneficial influence.